Studi Kelayakan Bisnis Pada Bisnis Fashion Hawa The Label - Nurjihan, Mumtazah; Hestiyanti, Siti Fatimah; Solekah, Nihayatu Aslamatis (Maliki Interdisciplinary Journal, 2025)
This study evaluates the business feasibility of Hawa The Label, a Muslim fashion brand, based on seven main aspects: legal, environmental, market, technical, management, financial, and AMDAL. The results of the analysis show that Hawa The Label has a large market potential, an effective digital marketing strategy, and attractive product design. Although this business still requires complete licensing, its environmental impact is relatively minimal with opportunities to improve sustainability practices. Technically, collaboration with convection partners and the use of technology support operational efficiency. Business finances show positive prospects with a fast return on investment. Overall, Hawa The Label is considered feasible to run and has the potential to develop in both local and international markets, with recommendations to complete licensing and strengthen environmental sustainability.